Impact of co-exposure to Chaetoceros spp. and Tenacibaculum maritimum on Atlantic salmon (Salmo salar) gills - E. Fajei; S.K. Whyte; M. Soto-Davila; K. Eslamloo; L. Groves; K. Storey; R. Ghanei-Motlagh; D.B. Groman; S.L. Purcell; M.D. Fast (Aquaculture, 2026)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A landscape‐scale framework to identify refugia from multiple stressors - Isabel M. Rojas; Megan K. Jennings; Erin Conlisk; Alexandra D. Syphard; Jack Mikesell; Alicia M. Kinoshita; Krista West; Doug Stow; Emanuel Storey; Mark E. De Guzman; Diane Foote; Alexandria Warneke; et al. (Conservation Biology, 2022)
From a conservation perspective, quantifying potential refugial capacity has been predominantly focused on climate refugia, which is critical for maintaining the persistence of species and ecosystems. However, protection from other stressors, such as human‐induced changes in fire and hydrology, that cause habitat loss, degradation, and fragmentation is also necessary to ensure that conservation efforts focused on climate are not undermined by other threats. Thus, conceptual and methodological advances for quantifying potential refugia from multiple anthropogenic stressors are important to support conservation efforts. We devised a new conceptual approach, the domains of refugia, for assessing refugial capacity that identifies areas where exposure to multiple stressors is low. In our framework, patterns of environmental variability (e.g., increased frequency of warm summers), thresholds of resilience, and extent and intensity of stressors are used to identify areas of potential refugia from a suite of ongoing anthropogenic stressors (e.g., changes in fire regime). To demonstrate its utility, we applied the framework to a Southern California landscape. Sites with high refugial capacity (super‐refugia sites) had on average 30% fewer extremely warm summers, 20% fewer fire events, 10% less exposure to altered river channels and riparian areas, and 50% fewer recreational trails than the surrounding landscape. Our results suggest that super‐refugia sites (∼8200 km 2 ) for some natural communities are underrepresented in the existing protected area network, a finding that can inform efforts to expand protected areas. Our case study highlights how considering exposure to multiple stressors can inform planning and practice to conserve biodiversity in a changing world.

U–Pb isotopic dating of titanite microstructures: potential implications for the chronology and identification of large impact structures - K. Papapavlou; J. R. Darling; D. E. Moser; I. R. Barker; L. F. White; P. C. Lightfoot; C. D. Storey; J. Dunlop (Contributions to Mineralogy and Petrology, 2018)

An Experimental and Numerical Investigation of CO2 Distribution in the Upper Airways During Nasal High Flow Therapy - S. C. Van Hove; J. Storey; C. Adams; K. Dey; P. H. Geoghegan; N. Kabaliuk; S. D. Oldfield; C. J. T. Spence; M. C. Jermy; V. Suresh; J. E. Cater (Annals of Biomedical Engineering, 2016)

Rheomorphic ignimbrites of the Rogerson Formation, central Snake River plain, USA: record of mid-Miocene rhyolitic explosive eruptions and associated crustal subsidence along the Yellowstone hotspot track - Thomas R. Knott; Marc K. Reichow; Michael J. Branney; David R. Finn; Robert S. Coe; Michael Storey; Bill Bonnichsen (Bulletin of Volcanology, 2016)

Transcript expression of the freeze responsive gene fr10 in Rana sylvatica during freezing, anoxia, dehydration, and development - K. J. Sullivan; K. K. Biggar; K. B. Storey (Molecular and Cellular Biochemistry, 2015)

Divergent muscle functional and architectural responses to two successive high intensity resistance exercise sessions in competitive weightlifters and resistance trained adults - Adam Storey; Samantha Wong; Heather K. Smith; Paul Marshall (European Journal of Applied Physiology, 2012)

HIF-1α regulation in mammalian hibernators: role of non-coding RNA in HIF-1α control during torpor in ground squirrels and bats - Yulia Maistrovski; Kyle K. Biggar; Kenneth B. Storey (Journal of Comparative Physiology B, 2012)

A multi‐scale segmentation approach to filling gaps in Landsat ETM+ SLC‐off images - S. K. Maxwell; G. L. Schmidt; J. C. Storey (International Journal of Remote Sensing, 2007)

Cold-loving microbes, plants, and animals—fundamental and applied aspects - R. Margesin; G. Neuner; K. B. Storey (The Science of Nature, 2007)

UDP-sugar pyrophosphorylase is essential for pollen development in Arabidopsis - Judy A. Schnurr; Kathleen K. Storey; Hans-Joachim G. Jung; David A. Somers; John W. Gronwald (Planta, 2006)

Influence of type of cancer and hematopoietic stem cell transplantation on clinical presentation of Pneumocystis jiroveci pneumonia in cancer patients - H. A. Torres; R. F. Chemaly; R. Storey; E. A. Aguilera; G. M. Nogueras; A. Safdar; K. V. I. Rolston; I. I. Raad; D. P. Kontoyiannis (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

Effects of hibernation on multicatalytic proteinase complex in thirteen-lined ground squirrels, Spermophilus tridecemlineatus - Ashley K. Woods; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2005)

Freezing survival, body ice content and blood composition of the freeze-tolerant European common lizard, Lacerta vivipara - Voituron Y.; Storey J.; Grenot C.; Storey K. (Journal of Comparative Physiology B, 2002)

Seasonal change and prolonged anoxia affect the kinetic properties of phosphofructokinase and pyruvate kinase in oysters - S. C. Greenway; K. B. Storey (Journal of Comparative Physiology B, 2000)

Discordant responses of mitogen-activated protein kinases to anoxia and freezing exposures in hatchling turtles - S. C. Greenway; K. B. Storey (Journal of Comparative Physiology B, 1999)

Cyclic AMP-dependent protein kinase: role in anoxia and freezing tolerance of the marine periwinkle Littorina littorea - J. A. MacDonald; K. B. Storey (Marine Biology, 1999)

cAMP-dependent protein kinase from brown adipose tissue: temperature effects on kinetic properties and enzyme role in hibernating ground squirrels - J. A. MacDonald; K. B. Storey (Journal of Comparative Physiology B, 1998)

Antioxidant defenses and lipid peroxidation damage in estivating toads, Scaphiopus couchii - J. E. Grundy; K. B. Storey (Journal of Comparative Physiology B, 1998)